2019
DOI: 10.1093/nar/gkz813
|View full text |Cite
|
Sign up to set email alerts
|

Alliance of Genome Resources Portal: unified model organism research platform

Abstract: The Alliance of Genome Resources (Alliance) is a consortium of the major model organism databases and the Gene Ontology that is guided by the vision of facilitating exploration of related genes in human and well-studied model organisms by providing a highly integrated and comprehensive platform that enables researchers to leverage the extensive body of genetic and genomic studies in these organisms. Initiated in 2016, the Alliance is building a central portal (www.alliancegenome.org) for access to data for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 18 publications
0
94
0
Order By: Relevance
“…the screen also showed that ubiquitous somatic moody knockdown using two different UASmoody hairpin lines resulted in dramatic increase in GSC loss compared to control RNAi (Table 1), suggesting a potential role for moody in GSC maintenance. moody encodes an orphan neuropeptide receptor (homolog of human melatonin receptor 1A and 1B, MTNR1A and MTNR1B [29]) required for integrity of the blood-brain barrier [30,31] and with no known roles in oogenesis. To follow up on the screen results suggesting a role for moody in GSC maintenance, we first performed RT-qPCR (using RNA from whole flies) to measure knockdown efficiency of the three UAS-moody hairpin lines expressed in the soma, which target distinct regions of moody ( Fig 3A).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…the screen also showed that ubiquitous somatic moody knockdown using two different UASmoody hairpin lines resulted in dramatic increase in GSC loss compared to control RNAi (Table 1), suggesting a potential role for moody in GSC maintenance. moody encodes an orphan neuropeptide receptor (homolog of human melatonin receptor 1A and 1B, MTNR1A and MTNR1B [29]) required for integrity of the blood-brain barrier [30,31] and with no known roles in oogenesis. To follow up on the screen results suggesting a role for moody in GSC maintenance, we first performed RT-qPCR (using RNA from whole flies) to measure knockdown efficiency of the three UAS-moody hairpin lines expressed in the soma, which target distinct regions of moody ( Fig 3A).…”
Section: Plos Onementioning
confidence: 99%
“…(MTNR1A and MTNR1B) [29], which bind melatonin, a key regulator of circadian rhythm in vertebrates [66]. Like moody, melatonin receptors are expressed throughout the body, including in the central nervous system and in peripheral tissues such as the intestine, adipocytes, immune cells, epithelial tissues, ovary/granulosa cells, and myometrium [67].…”
Section: Plos Onementioning
confidence: 99%
“…Examples of the accomplishments of the Alliance to date include: (i) a single integrated Alliance orthology gene set for comparative genomics of humans and model organisms, based on the work of the Quest for Orthologs Consortium (Glover et al 2019); (ii) adoption of the Disease Ontology as the common annotation standard for annotating human disease association; (iii) a ribbon visualization widget to display summary annotations for gene function, phenotype, and expression developed initially by the MGD (Bult et al 2016) that has been implemented by Alliance developers as a reusable web component for displaying annotations across multiple organisms, and (iv) a computational method developed by WormBase for automatically generating brief, readable summaries of gene function from ontology annotations, which is now used across the Alliance members to generate gene summaries for model organisms and human. A recent publication on the functionality currently supported by the Alliance website illustrates how researchers can search the resource by gene symbols, gene function terms, and disease terms, and then review annotations from all six model organisms and human using interfaces that share a common look and feel (Alliance of Genome Resources Consortium 2019).…”
Section: The Alliance Of Genome Resourcesmentioning
confidence: 99%
“…For example, the International Mouse Phenotyping Consortium (IMPC) [3] aims to associate phenotypes with loss of function mutations using gene knockout experiments, and similar knockout experiments have been performed in several model organisms [4]. Further genotype-phenotype associations for the laboratory mouse and other model organisms are also systematically extracted from literature and recorded in model organism databases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%